New insights into embayed beach rotation: The importance of wave exposure and cross‐shore processes. Issue 8 (6th August 2015) - Harley, M. D.; Turner, I. L.; Short, A. D.
Abstract: Although embayed beach rotation has been viewed and modeled as an alongshore sediment transport process acting on a uniform beach profile, recent research suggests a more complex response whereby alongshore variability in cross‐shore sediment fluxes may be more significant. This study utilizes 5 years of fully three‐dimensional beach surveys at Narrabeen‐Collaroy Beach (SE Australia) to quantify the control of alongshore nonuniform wave exposure and cross‐shore processes on embayed beach rotation. Empirical orthogonal function analysis of the alongshore variability in subaerial beach volume/width and berm slope confirms that the dominant mode of subaerial beach variability is an onshore/offshore sediment exchange that is strongly controlled ( R > 0.8) by the alongshore gradient in breaker wave height and coincides with a uniform flattening/steepening of the berm slope. A secondary rotation‐like signal is observed in both the subaerial beach volume/width data and, significantly, the berm slope. This inverse flattening/steepening of the berm slope between beach extremities is most likely a proxy for differing cross‐shore processes within the surf zone between the exposed and sheltered ends of the embayment, particularly with regards to dissipation of storm wave energy by offshore sandbars and beach recovery following storms. Analysis of the corresponding wave data reveals two distinct time scales of wave forcing characteristic of short‐term erosion and longer‐term recovery processes. A new conceptual model is presented of three differing modes of embayed beach rotation, with the newly identified beach rotation mode controlled by offshore sandbars considered of particular importance at embayments where headland sheltering of oblique waves is pronounced. Key Points: Three‐dimensional beach surveys used to determine alongshore nonuniform processes controlling beach rotation Three rotation modes observed, including new mode influenced by offshore sandbars Two time scales of wave forcing found due to different erosion/recovery cycles between extremities